2002
DOI: 10.1007/bf03324426
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive decline is related to education and occupation in a Spanish elderly cohort

Abstract: Cognitive decline in the elderly is partially explained by early life events, such as education, and living in a deprived environment over a long period of time. We cannot ascertain whether these effects are direct or mediated by other associated conditions but sample attrition does not account for our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 39 publications
4
36
1
3
Order By: Relevance
“…Consistent with previous studies, our study found that people with unskilled blue-collar work were more likely to have MCI [40,41]. Li et al [42] reported that as compared to the highest position, all of the three lower positions showed higher risks of cognitive impairment with the relative risk estimates ranging from 1.2 to 2.4.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with previous studies, our study found that people with unskilled blue-collar work were more likely to have MCI [40,41]. Li et al [42] reported that as compared to the highest position, all of the three lower positions showed higher risks of cognitive impairment with the relative risk estimates ranging from 1.2 to 2.4.…”
Section: Discussionsupporting
confidence: 80%
“…Epidemiological studies have shown lower prevalence or incidence of dementia in elder population with high level of education (see Meng andD"Arcy, 2012 andValenzuela et al, 2006 for a review and meta-analysis). Furthermore, neuropsychological studies have reported better cognitive test performance (Plassman et al, 1995;Wilson et al, 2009) and reduced rate of cognitive decline (Albert et al, 1995;Alvarado et al, 2002;Anstey et al, 2003;Christensen et al, 1997;Evans et al, 1993;Farmer et al, 1995;Lyketsos et al, 1999;White et al, 1994) in elders with higher levels of education. These investigations suggest that education affects the risk of late life dementia by its positive association with level of cognition or through its association with decreased rate of cognitive decline in aging.…”
Section: Introductionmentioning
confidence: 99%
“…La démence est devenue un véritable problème de santé publique. Sa prévalence augmente considérablement avec l'âge et l'instruction [4,8,13]. Elle a un impact sur le système social, l'économie, la santé.…”
Section: Introductionunclassified